Monitoring of Training Load and Body Composition in Elite Male Kayakers - José Augusto Rodrigues dos Santos; Giorjines Boppre; Rodrigo Zacca (Applied Sciences)
Background: Elite kayaking demands peak conditioning, and tracking these athletes reveals the science behind world-class performance. Physiological demands and body composition changes in elite male kayakers were tracked during the preparatory and transition periods of a kayaking competitive season. Methods: Laboratory (body composition assessment and a 4 min all-out test in a kayak ergometer) on-field tests (4 × 1500 m incremental intermittent protocol with 30 s rest intervals in a kayaking/rowing track) were applied on separate days to follow eight elite male kayakers (23.1 ± 5.6 y; 80 ± 8.8 kg; 177.0 ± 6.8 cm) at the beginning of the kayaking season (preparatory period, M1; first week of October), 22 weeks later, at the beginning of the transition period (M2; last week of February), and 5 weeks later, at the end of the transition period, i.e., beginning of the competitive period of the season (M3; first week of April). M3 corresponded to the participation in international competitions. Results: Distance at peak oxygen uptake (<semantics><mover accent="true">V˙</mover>O2peak</semantics>) on the kayak ergometer improved by 36.7 m from M1 to M3, the pace at V4 (aerobic capacity) was reduced (improved) by 25.2 s·km−1 from M1 to M2, and 25.6 s·km−1 by M3. Body weight decreased by 2.3 kg from M1 to M2, and fat mass percentage and kilograms decreased by 1.8% and 3.1%, respectively. Fat-free mass increased by 1.9% and 3.1%, respectively. Skinfold measurements showed a decrease in subscapular, suprailiac, abdominal, and geminal skinfold. Aerobic power (<semantics><mover accent="true">V˙</mover></semantics>O2peak) in absolute values (in L·min−1) improved by 0.7 L·min−1 from M1 to M2, and by 1.1 L·min−1 by M3, and from M2 to M3 was ~0.5 L·min−1. Aerobic power in relative values improved by 15.0 from M1 to M2, and by 6.4 mL·kg−1·min−1 from M2 to M3. Conclusions: Elite male kayakers improved their physiological performance and body composition during the preparatory and transition phases of the competitive season. Notable gains in performance were mainly due to enhanced aerobic power, and positive body composition changes. These findings provide insights for optimizing training strategies and boosting competitive performance.